Synthesis and Evaluation of Al2O3_Mg/AA6061 Aluminium Foam Composite via Compaction and Sintering - Singh, Devendra; Mayank Agarwal, (International Journal of Scientific Research and Management (IJSRM), 2021)
In this paper compressive behaviour of an Aluminium foam composite have been evaluated and discussed. The outcome reflects that quasi static stress –strain curve of Al composite was same as to Al foams. However, within the two strain ranges from strain less than 0.03 and strain greater than 0.2, the ideal absorption energy of the composites was higher than that of parent Al foams. When the strain ranged from 0.03 to 0.2 the ideal energy absorption efficiency value of the composite was lower than the Al foams.There are many methods for fabricating metal foams but we preferred powder metallurgy process. This process of production allows for the production of complex shaped foam parts. Many alloys including Aluminium, zinc, tin, lead and steel can be produced using this method. The fabricated part has a closed cell microstructure and a high fraction of porosity. Mechanical properties foams are evaluated including the axial crushing, Hardness and toughness test are also carried out. Applications are such as light weight construction and energy absorption for civilians as well as military uses.